Disease severity assessment and short-term outcome in patients with myasthenia gravis - Deepthi Vemuri (Annals of Indian Academy of Neurology, 2020)
Background: Myasthenia gravis (MG) is an autoimmune disorder with a chronic fluctuating course. The outcome measures encapsulate disease severity, functional impact at diagnosis, and objective evaluation of clinical benefit from therapeutic interventions.Aims and Objective: To assess the disease severity, correlation between various outcome measures, and to evaluate the short-term outcome at 3 months and 6 months in a cohort of MG patients.Materials and Methods: Quantitative myasthenia gravis (QMG) score, myasthenia gravis composite (MGC) score, and myasthenia gravis quality of life-15 (MG-QoL-15) score were applied to 54 patients at first visit, 3 months and 6 months follow-up.Results: Mean quality of life-15 (QoL-15) score at base line was 15.241. Mean QMG and MGC scores at baseline were 14.63 ± 8.37 and 15.87 ± 9.14, respectively. QMG score showed a strong positive correlation with both MGC and MG-QoL-15 scores. QMG and MGC scores showed a moderate correlation with acetylcholine receptor antibody (AChR Ab) titers. Mean QMG at follow-up was 9.95 ± 5.49 at 3 months and 6.74 ± 4.74 at 6 months. Mean MGC at follow-up was 10.75 ± 5.58 at 3 months and 6.51 ± 4.36 at 6 months. Conclusion: The combination of physician-evaluated and patient-reported outcome measures provided a more discerning picture of patient status and response to treatment. Incorporating MG outcome measures into clinical practice would aid in modulating therapies.